EVALUASI KEBIJAKAN PROGRAM BANTUAN STIMULASI PERUMAHAN SWADAYA DI KABUPATEN BUTON SELATAN - Arifin Utha; Justawan; Marlita (Halu Oleo University, 2022)
The purpose of this study was to determine the implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) in South Buton Regency. The method used by researchers is a qualitative research method through observation, interviews and documentation. The number of informants in this study were four people from the government of Lapandewa Jaya Village, and three people from the community as recipients of self-supporting housing stimulation assistance. The results in this study indicate that the implementation of self-help housing stimulation assistance in Lapandewa Jaya Buton Selatan Village still has several obstacles, namely during the implementation process the recipient provides help from workers or labor from other people who are paid, while there is no budget for renting construction workers, as well as a relatively low budget. small to build thus affecting the quality and time to build, so what the government needs to continue to encourage at this time is evaluating the recipients of Self-Help Housing Stimulation Assistance and ascertaining how many other low-income people who cannot afford to have livable homes to be proposed as candidates for assistance recipients Stimulation of the next stage of Self-Help Housing.